Heat Transfer Characteristics for Practical Hydrogen Pressure Vessels Being Filled at High Pressure - Peter L. WOODFIELD; Masanori MONDE; Toshio TAKANO (Journal of Thermal Science and Technology, 2008)
Experiments have been conducted to measure the rise in temperature of hydrogen and vessel wall during filling of commercially available, practical tanks to 35 and 70 MPa. Three test vessels with volumes 205, 130 and 39 liters are investigated. The filling time ranges from 5 to 20 minutes. The heat transfer process is modeled using a one-dimensional unsteady heat conduction equation for the wall coupled with a flow and heat balance for the compressed gas. The model requires heat transfer coefficients between the hydrogen and the wall and the wall and surrounding air. Values of 500 W/(m2K) during filling, 250 W/(m2K) after filling for the inside wall and 4.5 W/(m2K) for the outside tank wall are tentatively assumed based on results from a previous study on a smaller vessel. The measured temperatures for the hydrogen gas and the wall are in good agreement with the calculations.